The direction of the historical and leninist marxist education in the context of the pedagogical universities - Lidia Cira Carbonell Izquierdo; Magdalena Cruz Estrella (Revista MENDIVE, 2013)
This article analyzes a strategic conception to direct the historical and Leninist Marxist education in Pinar del Río, because it constitutes nowadays one of the maximum priority problems in the daily activities of the pedagogic universities, for which it is needed a development of the learning levels of History and of Marxism Leninism, based on a solid political and ideological preparation of the graduates in these institutions.